Phylogeny and biogeography of the amphi-Pacific genus Aphananthe. - Mei-Qing Yang; De-Zhu Li; Jun Wen; Ting-Shuang Yi (PLoS ONE)
Aphananthe is a small genus of five species showing an intriguing amphi-Pacific distribution in eastern, southern and southeastern Asia, Australia, and Mexico, also with one species in Madagascar. The phylogenetic relationships of Aphananthe were reconstructed with two nuclear (ITS & ETS) and two plastid (psbA-trnH & trnL-trnF) regions. Clade divergence times were estimated with a Bayesian approach, and the ancestral areas were inferred using the dispersal-extinction-cladogenesis and Bayesian Binary MCMC analyses. Aphananthe was supported to be monophyletic, with the eastern Asian A. aspera resolved as sister to a clade of the remaining four species. Aphananthe was inferred to have originated in the Late Cretaceous (71.5 mya, with 95% HPD: 66.6-81.3 mya), and the crown age of the genus was dated to be in the early Miocene (19.1 mya, with 95% HPD: 12.4-28.9 mya). The fossil record indicates that Aphananthe was present in the high latitude thermophilic forests in the early Tertiary, and experienced extinctions from the middle Tertiary onwards. Aphananthe originated in Europe based on the inference that included fossil and extant species, but eastern Asia was estimated to be the ancestral area of the clade of the extant species of Aphananthe. Both the West Gondwanan vicariance hypothesis and the boreotropics hypothesis could be excluded as explanation for its amphi-Pacific distribution. Long-distance dispersals out of eastern Asia into North America, southern and southeastern Asia and Australia, and Madagascar during the Miocene account for its wide intercontinental disjunct distribution.